Memahami Al-Lahn dan Signifikansi Kodifikasi Ilmu Nahwu dalam Bahasa Arab - Bahri, Samsul (el Buhuth: Borneo Journal of Islamic Studies, 2024)
The aim of this research is to describe understanding al-lahn and the significance of the codification of nahwu science in Arabic. Historically, before the arrival of Islam, Arab people did not know the science of nahwu because during the period of ignorance they spoke using fusha Arabic with their saliqah so that they were free from language errors in communicating. The mixing of Arabs and Muslims with non-Arab nations and communities resulted in the spread of land among the people. The phenomenon of land spread is not only in the language of communication, but extends to reading the Koran and the Hadith of the Prophet. This land phenomenon does not only affect the general public but also among the educated. This made the scholars who felt jealous of the Arabic language called to codify the science of grammar to prevent oral language from being spoken, this science of grammar became known as the science of Nahwu.